Prediction of genetic gains and correlations in corn hybrids for silage - Crevelari, Jocarla Ambrosim; Durães, Nayara Norrene Lacerda; Bendia, Laila Cecília Ramos; da Silva, Alysson Jalles [UNESP]; Pereira, Messias Gonzaga (Southern Cross Publishing, 2017)
During the dry season the production of pastures dicreases. Usually, it makes the situation necessary to use corn silage as fibrous fodder source. The aim of this study was to develop corn hybrids for silage production, prioritizing hybrid combinations of the heterotic group 'DENT' to better understand the association between the evaluated traits and to optimize the selection process by using selection indices. Nineteen topcross hybrids and five controls were evaluated in a complete randomized block design with four and five replications in the agricultural years of 2013 and 2014. The following traits were evaluated: plant height, first ear height, stem diameter, yield at silage stage, ear yield with and without straw at silage stage, fresh mass yield, and proportion of grains in the fresh mass. The highest coefficients of correlation were obtained between yield and ear yield with straw (r = 0.94**), and between ear yield with straw and fresh mass yield (r = 0.89**). The Mulamba & Mock selection index was used for prediction of genetic gains. For selection of the superior hybrids, the index resulted in higher estimates of predicted gains for yield at silage stage and fresh mass yield, with values of 6.13 and 4.46%, respectively, using weights assigned. The use of selection indices allows simultaneous prediction of gains in the two main traits. Topcross hybrids presented high potential for silage yield in the North and Northwest Regions.
Keywords: Index; Selection; Tester; Topcross; Zea mays L